POJOK BACA SEBAGAI JEMBATAN MEMBENTUK KARAKTER CINTA BUKU DAN TANGGUNG JAWAB PADA ANAK TK KELAS B - Milawati; A. Suriansyah; Amalia, Rizky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This case study aims to analyze the role of the reading corner in shaping the character of love for books and responsibility among Kindergarten B children at a PAUD institution in Alalak District. The reading corner, equipped with illustrated storybooks, serves as the main medium in this process. Observations and interviews revealed that the presence of an attractive reading corner, supported by the teacher's initiative in reading books both directly and through digital media (LCD), successfully fosters children's interest in reading. Although they are not yet able to read text, the children begin to “read pictures” and retell the story using their own language—even some confidently read stories aloud to their peers. This indicates the development of a love for books. A sense of responsibility is also nurtured through the habit of independently or collaboratively returning and organizing books in the reading corner. This study highlights the importance of a supportive literacy environment and the active role of teachers in instilling character values from an early age.